Analisis Technological Pedagogical Content Knownledge (TPACK) dan Content Representation (CoRes) Sebagai Upaya dalam Meningkatkan Efektifitas Pembelajaran Materi Genetika di Sekolah - Arif Sura, Sunarto; Syahirah, St Syahirah; Venty, Venty Sugih Hartini; Rahmat, Adi; Riandi (Pedagogi Hayati, 2024)
Education plays a critical role in developing the potential of each individual, and the quality of the teaching and learning process is vital for the success of the education undertaken by students. Innovative learning designs that meet student needs are required. Genetic material in biology, which is complex and conceptual, requires deep understanding. Therefore, it is important for educators to use teaching strategies that allow students to better understand genetic concepts. The purpose of this study is to evaluate genetic teaching strategies including curriculum analysis, approaches, and the application of various models, methods, and media in learning. This research method is qualitative with a descriptive approach, aiming to describe current genetic teaching practices, including the use of TPACK by teachers. Data was collected through literature study with stages such as data collection, organization, analysis, interpretation, and conclusion with descriptive qualitative data analysis. The analysis results were verified by experts. The findings show that teachers have implemented various approaches, models, methods, and learning media. The success of the learning process greatly depends on effective teacher planning so that students can clearly understand the material. These findings provide useful information for teachers to implement TPACK in genetics learning.